University students' and clinicians' beliefs and attitudes towards physical activity for mental health. (March 2020) - deJonge, Melissa L.; Omran, Janine; Faulkner, Guy E.; Sabiston, Catherine M.
Abstract: Objective: Post-secondary campuses provide students with a range of physical activity resources and programs. Despite the wide-ranging and accessible nature of on-campus physical activity and exercise facilities, limited research has explored physical activity as a treatment for poor mental health within the post-secondary context. The current study aimed to explore students' and mental health stakeholders' beliefs and attitudes towards physical activity for mental health. Methods: Semi-structured individual interviews were conducted with students experiencing depressive symptoms ( N = 15) and with mental health stakeholders (i.e., mental health counsellors, psychiatrists and the lead director of mental health services; N = 5) from a large Canadian university. The interviews were analyzed separately using a data-driven inductive thematic analysis, and then cross-referenced to generate common themes. Results: Mental health stakeholders voiced their attitudes and beliefs on clinical discussions of physical activity for mental health, while students discussed their uptake to physical activity for mental health. Comparable themes broadly situated attitudes and beliefs within positive perceptions of physical activity as a unique mental health support; barriers that influence clinical discussions and student uptake; and strategies to facilitate clinical discussions and student uptake. Taken together, the discussions portrayed a need for accessible resources and programs specifically tailored towards physical activity for mental health. Conclusions: The findings highlight the acceptability of physical activity as a mental health intervention tool within a post-secondary context. Importantly the results provide implications for developing strategies to incorporate physical activity as an acceptable support method within mental health services. Highlights: The acceptability of physical activity for student mental health is demonstrated. A gap in the implementation of physical activity in mental health care is evident. Collaborative efforts between exercise and mental health professionals are needed. Context specific implementation strategies and knowledge-based resources are needed.